An Analysis of Taking the Turn in Talk Show “Piers Morgan Uncensored” - Fadil Juliano; Afriana Afriana (LPPM Universitas Bumigora Mataram, 2024)
The aim of this research is to identify turn-taking strategies in terms of taking turns. The turn-taking strategies involve three basic strategies: taking the turn, holding the turn, and yielding the turn. In this research, the researchers focused on the taking-the-turn strategy. The data source was Piers Morgan's interview with Andrew Tate. Stenström framework was used to analyze the data in this study. The qualitative method is used in this research. In collecting data, this research used the observational method. Meanwhile, the technique of collecting data was a note-taking technique. Furthermore, the researchers used the referential identity method in analyzing data; in presenting the result of the research, the researchers utilized the informal method. The research results show that three types of turn-taking strategies in the data source. They are starting up, taking over, and interrupting. Based on the research, interrupting occurs six times, taking over occurs six times, and starting up occurs three times. Starting up is the lowest type that occurs in this data because the two speakers are good talkers who rarely use fillers. Interrupting is the most common type in this data because the two speakers have high conversational proficiency, demonstrating fluency. The implication of this study is to advance the understanding of turn-taking strategies in a new and unexplored context and highlight the strategic use of language in media discourse.